The Effectiveness of Magnetism Recitation Program to Improve Students' Understanding Concepts on Topic Magnetism - Shodiqin, Muhammad Ibnu; Sutopo; Edi Supriana; Dwi Rokhmatin (BRILIANT: Jurnal Riset dan Konseptual, 2024)
Students often experience difficulties in mastering physics concepts, especially on the topic of magnetism due to inaccurate understanding and misconceptions. Limited learning time is also a factor that hinders in-depth understanding. To overcome this problem, a web-based recitation method was developed using the Moodle platform to help improve students' mastery of concepts. This research developed a recitation program called the Magnetism Recitation Program (MRP) and can be accessed using a smartphone or laptop with an internet network. MRP contains multiple choice questions with direct feedback that are tailored to various student thinking possibilities. This research aims to determine the effectiveness of MRP. To answer the objectives, this research used a one-group pretest-posttest design involving 25 Physics Education students at the State University of Malang who were taking the Basic Physics III course. The effectiveness of MRP is analyzed using the n-gain value. The research results show an n-gain value of 0.22, which means that MRP is effective in increasing students' mastery of concepts on the topic of magnetism, although there are several weaknesses that students still experience.